Maqashid Nikah Menurut Imam Al Ghazali Dalam Kitab Ihya Ulumuddin - Moch. Azis Qoharuddin; Purnomo (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The purpose of doing this research is to find out about the purpose and purpose of marriage applied by Imam Ghazali in the book of Ihya' Ulumuddin. Judging from the type of research is classified as library research, which is theoretical and philosophical. Its research methods include data sources and data collection. The method of data collection is done by means of literature studies. The method of data analysis using the deductive thinking method is to draw conclusions from a problem based on things or events that are common to a specific conclusion. Let the husband and wife before marriage study the science of religion related to marriage so that each right can be exercised, because how can he know the rights of each other if without the basis of religious knowledge. By knowing the science of religion, God willing the family will be awake from the fire of Hell. Let a husband patiently face the treatment or akhlaq of an unwise wife, for no matter what reason a woman is not equal to the man's mind.